2020
DOI: 10.14814/phy2.14540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrical stimulation‐induced resistance exercise training on white and brown adipose tissues and plasma meteorin‐like concentration in rats

Abstract: Chronic endurance exercise training induces morphological and metabolic alterations including mitochondrial biogenesis in white adipose tissue (WAT) and brown adipose tissue (BAT) in rodents. A myokine called meteorin‐like (Metrnl) is associated with morphological and metabolic adaptation and increased in blood after acute resistance exercise. However, the effects of chronic resistance exercise training (RT), which aims to increase muscle mass and strength, on WAT and BAT are unclear. Therefore, we aimed to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…PGC-1a4 is an exercise-induced splice isoform of PPARg coactivator 1a, where Metrnl was regarded as its downstream effector protein. A recent study reported by Amano et al (136) supported this effector pathway of PGC-1a along with Metrnl. After they applied 4-week electrical stimulation to rats' legs, which aimed to simulate chronic resistance exercise, an apparent positive correlation was found between the expression of PGC-1a in brown adipose tissues and plasma Metrnl levels.…”
Section: Metrnl and Exercisementioning
confidence: 64%
“…PGC-1a4 is an exercise-induced splice isoform of PPARg coactivator 1a, where Metrnl was regarded as its downstream effector protein. A recent study reported by Amano et al (136) supported this effector pathway of PGC-1a along with Metrnl. After they applied 4-week electrical stimulation to rats' legs, which aimed to simulate chronic resistance exercise, an apparent positive correlation was found between the expression of PGC-1a in brown adipose tissues and plasma Metrnl levels.…”
Section: Metrnl and Exercisementioning
confidence: 64%
“…Interestingly, exercise in combination with DHA was able to reverse the decreased expression observed in the DHA alone group. Exercise also induces Metrnl expression in skeletal muscle [ 16 ] and studies in exercise-performing mice have found increases in muscle Metrnl protein, serum levels and/or Metrnl mRNA [ 16 , 120 , 126 , 127 ]. However, we found no significant changes in Metrnl expression due to exercise in comparison with the DIO mice.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, resistance training induces a significant reduction of body weight and subcutaneous and epididymal white adipose tissue, but the brown adipose tissue is not affected by training. After training, animals showed smaller adipocytes [537].…”
Section: Effect Of Physical Exercise On Adipose Tissue and Other Body...mentioning
confidence: 97%